Use of physiologically‐based pharmacokinetic modeling to inform dosing of the opioid analgesics fentanyl and methadone in children with obesity - Jacqueline G. Gerhart; Fernando O. Carreño; Jennifer L. Ford; Andrea N. Edginton; Eliana M. Perrin; Kevin M. Watt; William J. Muller; Andrew M. Atz; Amira Al‐Uzri; Paula Delmore; Daniel Gonzalez; Best Pharmaceuticals for Children Act–Pediatric Trials Network Steering Committee (CPT: Pharmacometrics & Systems Pharmacology, 2022)
Abstract Obesity is an increasingly alarming public health threat, with nearly 20% of children classified as obese in the United States today. Children with obesity are commonly prescribed the opioids fentanyl and methadone, and accurate dosing is critical to reducing the risk of serious adverse events associated with overexposure. However, pharmacokinetic studies in children with obesity are challenging to conduct, so there is limited information to guide fentanyl and methadone dosing in these children. To address this clinical knowledge gap, physiologically‐based pharmacokinetic models of fentanyl and methadone were developed in adults and scaled to children with and without obesity to explore the interplay of obesity, age, and pharmacogenomics. These models included key obesity‐induced changes in physiology and pharmacogenomic effects. Model predictions captured observed concentrations in children with obesity well, with an overall average fold error of 0.72 and 1.08 for fentanyl and methadone, respectively. Model simulations support a reduced fentanyl dose (1 vs. 2 μg/kg/h) starting at an earlier age (6 years) in virtual children with obesity, highlighting the importance of considering both age and obesity status when selecting an infusion rate most likely to achieve steady‐state concentrations within the target range. Methadone dosing simulations highlight the importance of considering genotype in addition to obesity status when possible, as cytochrome P450 (CYP)2B6*6/*6 virtual children with obesity required half the dose to match the exposure of wildtype children without obesity. This physiologically‐based pharmacokinetic modeling approach can be applied to explore dosing of other critical drugs in children with obesity.